Research on Crowdfunding Strategies of Family Farms in China - Lichen NIU; Nazarenko OLEKSANDR; Zetao HU; Yanjun FU (Communications of International Proceedings, 2021)
With the development of society, the Internet has played an important role in various fields. Internet finance has changed the traditional financial pattern, broadened the financial financing channels, and better catered to the needs of social and economic development. As a new type of agricultural operation subject, family farm financing is faced with the constraints of high access threshold, high financing cost and lack of sufficient collateral in the development process. With the development of economy and science and technology, Internet crowdfunding mode has been widely used. With the characteristics of low threshold, low cost and relatively transparent information, it provides a guarantee for the development of family farms. This paper takes family farm financing as the topic, analyzes the feasibility of crowdfunding financing mode of family farm, and puts forward relevant methods to inject vitality into family farm financing and promote better development.
Keywords: Internet Finance; Family Farm; Crowdfunding; Diversification.